Materials Effect in Sensing Performance Based on Surface Plasmon Resonance Using Photonic Crystal Fiber - Khalek, Md Abdul; Chakma, Sujan; Ahmed, Kawsar; Paul, Bikash Kumar; Vigneswaran, Dhasarathan; Zakaria, Rozalina (Springer Verlag (Germany), 2019)
This article explores the effect of sensing performances with subject to change in different types of material and this study is carried out by the support of plasmon-coated photonic crystal fiber (PCF). Three different materials gold, niobium, and doping materials (niobium and Al2O3) have been used as sensing materials to find out the best performance of the raised structure. Each material deposited sequentially on the PCF surface and the structural characterization is analyzed by finite element method (FEM).The investigation shows that it can provide the enhanced wavelength sensitivity of 5000 nm/RIU, 8000 nm/RIU, and 10,000 nm/RIU; and amplitude sensitivity of 171 RIU−1, 188 RIU−1, and 249 RIU−1 for gold, niobium, and doping materials, respectively, at analytes 1.37 and 1.38. In both cases, doping materials show best outcome. Moreover, the proposed model is also investigated to detect the change of phase matching point with the variation of center air hole diameter. The obtained results ensure that it may be helpful for any chemical or biological analytes detection. © 2018, Springer Science+Business Media, LLC, part of Springer Nature.